Program Pengampunan Pajak Di Indonesia: Peluang Dan Harapan Keberhasilannya - Setiadi Alim Lim; Lilik Indrawati (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2016)
Tax amnesty program is one instrument that is used widely by the tax authorities in many countries in order to increase tax revenue, broaden the tax base, improve tax compliance and other purposes. In addition to having a large role in increasing tax revenue, tax amnesty program also may be adversely affected as opposed to the benefits generated. Not all countries implement tax amnesty program success in implementing it. Experiences in the tax amnesty implementation in several countries showed that the program of tax amnesty are carried out several times and the implementation time was easily anticipated by the taxpayer generally not as successful if the program of tax amnesty is only a one-time, non-recurring and can not be anticipated time of its implementation by the taxpayer. In 2016 the Government of Indonesia to implement tax amnesty program that will be implemented starting on July 1, 2016 to March 31, 2017. After going through the analysis based on the experience of implementation of tax amnesty program conducted by several other countries can be predicted that the tax amnesty program implemented by the Government of Indonesia will be a success. Tax amnesty program implemented is estimated to have a great opportunity to meet the expectations of increasing tax revenue, broaden the tax base, improve tax compliance significantly. However, for the hope of repatriation of assets of the taxpayer from abroad into the country seems not to be able to meet expectations.